Psychoanalytic Criticism on song Lyrics Cancer by My Chemical Romance - Surbakti, Dea Evelyn; Soethama, Putu Lirishati; Laksminy, Luh Putu; Malini, Ni Luh Nyoman Seri Malini (Loquēla (Journal of Linguistics, Literature, and Education), 2024)
This research delves into the feelings experienced by the main character in the song "Cancer" by My Chemical Romance. This descriptive qualitative research aims to discover the anxiety and mental condition faced by a patient affected by cancer, as reflected in the song's lyrics, using Sigmund Freud's psychoanalytic theory as an approach. Data were collected by repeatedly listening to the song, understanding, and interpreting the literary work. The song "Cancer" by My Chemical Romance, without an accompanying music video, is the focus of the analysis, relying solely on the lyrics as the source. This approach involves understanding the meaning of the words, examining the emotional context, and exploring potential symbolism within the lyrics. The main goal of this research is to uncover and analyze the anxiety and mental journey of a patient affected by cancer through the lens of Freud's psychoanalytic theory. Through this research, it is hoped that a deeper understanding of the emotional and psychological dynamics faced by the main character in the song "Cancer" will be achieved and how Freud's psychoanalytic theory can assist in analyzing subconscious layers and psychological conflicts that may arise in the context of the song's lyrics. In conclusion, through the psychoanalytic lens, "Cancer" becomes an emotional narrative illustrating the dynamics between personality components in facing feelings of loss and death, creating a profound experience that feels personal and universal.